Flavonoids from the seeds of Oroxylum indicum and their anti-inflammatory and cytotoxic activities. (August 2019) - Wu, Bing-Lan; Wu, Zhou-Wei; Yang, Fan; Shen, Xiao-Fei; Wang, Lun; Chen, Bin; Li, Fu; Wang, Ming-Kui
Graphical abstract: Ten flavonoids, including two previously unreported, were isolated from the seeds of Oroxylum indicum. The isolates1 –10 were evaluated for their anti-inflammatory and cytotoxic activities. Highlights: Ten flavonoid glycosides including two new ones were characterized from Oroxylum indicum . Their structures were elucidated by NMR, mass spectrometry and chemical methods. Anti-inflammatory and cytotoxic activities of all compounds were evaluated. Abstract: Two new flavonoid glycosides, named oroxin C (1 ) and oroxin D (scutellarein 4'-methyl ether 7- O - β -D-glucopyranosyl-(1→6)- β -D-glucopyranoside, 2 ), together with eight known flavonoids (3 –10 ), were isolated from the seeds of Oroxylum indicum . Their structures were elucidated unambiguously by spectroscopic techniques and chemical methods. Anti-inflammatory and cytotoxic activities of all the isolated compounds were evaluated. Chrysin (3 ) and chrysin-6-C- β -D-glucopyranosyl-8-C- α -L-arabinopyranoside (10 ) showed moderate inhibitory effects aganist the LPS-induced NO production in murine RAW264.7 macrophages with IC50 values of 18.63 ± 0.91 and 28.69 ± 0.43 μ M, respectively. Chrysin (3 ) exhibited weak cytotoxic activity aganist A549, HepG2 and SW480 human cancer cell lines with IC50 values of 40.88 ± 3.85, 50.55 ± 2.59 and 91.60 ± 4.27 μ M, respectively.